Scalar dark matter multiplet of global O(N) symmetry - U-Rae Kim; Jungil Lee; Soo-hyeon Nam (Journal of High Energy Physics)
Abstract We study two types of models involving a scalar dark matter multiplet of global O(N) symmetry. These models are distinguished by the absence (Type I) or presence (Type II) of a scalar mediator with Z 2 symmetry. We derive the allowed regions for the dark matter mass and new scalar couplings based on constraints from Higgs invisible decay, the relic abundance of dark matter, and the spin-independent dark matter-nucleon scattering cross section. Within the allowed parameter space, we also discuss the vacuum stability of the Higgs potential and the perturbativity of the scalar couplings in both models. We find that the Type I model cannot achieve stable electroweak vacuum, whereas the Type II model can have both a stable vacuum and perturbative couplings up to the Planck scale.